Optimizing Recovery Following Critical Illness: A Systematic Review of Home-Based Interventions. Issue 2 (May 2023) - Holod, Alicia F.; Choi, JiYeon; Tate, Judith
Around 5 million Americans are treated in an intensive care unit (ICU) annually. Upon discharge, it is not uncommon for ICU survivors to experience psychological, physical, or cognitive symptoms related to their ICU stay. Home-based interventions have been touted as a potential treatment modality for post-ICU sequelae. However, limited evidence exists regarding the effectiveness of home-based interventions for patients in the post-ICU recovery period. As such, the purpose of this review was to aggregate and summarize the findings of studies focused on post-ICU rehabilitation, following critical illness, delivered in the home setting. A literature search was performed in MEDLINE, CINAHL, EMBASE, APA PsycINFO, and Google Scholar. Studies were included if they: used a RCT or quasi-experimental study design; included participants aged ≥18 years discharged home from an ICU; examined the effectiveness of a home-based, post-ICU intervention; were published in English after the year 2010; and were peer-reviewed. Nine studies met inclusion criteria. Sample sizes ranged from 21 to 386, with most participants receiving mechanical ventilation. Target outcomes included: physical function, psychological well-being, cognitive function, quality of life, and healthcare utilization. Interventions included face-to-face, web-based, telephone, or self-directed activities. Findings of included studies were mixed or inconclusive. Limitations of this review include: inclusion of only adult ICU survivors, exclusion of Post-Intensive Care Syndrome as a search term, and search restricted to pre-pandemic studies. Findings suggest a need for more rigorous research to develop and test home-based interventions.